Conceptual Study of Garbhini Paricharya as per Harita Samhita (AYUSHDHARA, 2021)
God has blessed the females with most valuable gift of motherhood. Ayurveda is the science which offers a specific routine to the pregnant woman and systematic supervision known as Garbhini Paricharya as pregnant woman’s diet and activities performed during the period of pregnancy reflect on the fetus. Hence in Ayurveda, our Acharyas have given great emphasis on Garbhini Paricharya or Antenatal care. Acharyas have thrown an immense light on the concept of type of diet, behaviour, conduct, medications during pregnancy that a pregnant woman should follow and avoid, known as Garbhini Paricharya. Basic objective of Garbhini Paricharya depicted in Ayurveda is to achieve a healthy progeny as well as to ensure the good health of mother and fetus during the period of pregnancy, during labor and in the postpartum period. In this paper we have described the monthly dietary regimen and lifestyle for whole nine months of pregnancy that is essential for the wellbeing of the growing fetus and pregnant woman according to Harita Samhita as well as the scientific aspects of the antenatal care. As antenatal care should be done in an integrated way i.e., as per modern science and as mentioned in Ayurvedic classics.